Limiting hepatic Bmp-Smad signaling by matriptase-2 is required for erythropoietin-mediated hepcidin suppression in mice - Nai, Antonella (Blood, 2016)
Hepcidin, the main regulator of iron homeostasis, is repressed when erythropoiesis is acutely stimulated by erythropoietin (EPO) to favor iron supply to maturing erythroblasts. Erythroferrone (ERFE) has been identified as the erythroid regulator that inhibits hepcidin in stress erythropoiesis. A powerful hepcidin inhibitor is the serine protease matriptase-2, encoded by TMPRSS6, whose mutations cause iron refractory iron deficiency anemia. Because this condition has inappropriately elevated hepcidin in the presence of high EPO levels, a role is suggested for matriptase-2 in EPO-mediated hepcidin repression. To investigate the relationship between EPO/ERFE and matriptase-2, we show that EPO injection induces Erfe messenger RNA expression but does not suppress hepcidin in Tmprss6 knockout (KO) mice. Similarly, wild-type (WT) animals, in which the bone morphogenetic protein–mothers against decapentaplegic homolog (Bmp-Smad) pathway is upregulated by iron treatment, fail to suppress hepcidin in response to EPO. To further investigate whether the high level of Bmp-Smad signaling of Tmprss6 KO mice counteracts hepcidin suppression by EPO, we generated double KO Bmp6-Tmprss6 KO mice. Despite having Bmp-Smad signaling and hepcidin levels that are similar to WT mice under basal conditions, double KO mice do not suppress hepcidin in response to EPO. However, pharmacologic downstream inhibition of the Bmp-Smad pathway by dorsomorphin, which targets the BMP receptors, improves the hepcidin responsiveness to EPO in Tmprss6 KO mice. We concluded that the function of matriptase-2 is dominant over that of ERFE and is essential in facilitating hepcidin suppression by attenuating the BMP-SMAD signaling.